Comparative population genomics analysis for chicken body sizes using genome-wide single nucleotide polymorphisms - Sensen Yan; Chaoqun Gao; Kaiyuan Tian; Chengpeng Xiao; Junlai Shi; Xintao Jia; Kejun Wang; Guirong Sun; Donghua Li; Wenting Li; Xiangtao Kang (Animal Bioscience)
Objective This study aims to investigate the selection history, genome regions, and candidate genes associated with different chicken body sizes, thereby providing insights into the genetic basis of complex economic traits such as chicken body size and growth. Methods In this study, a total of 217 individuals from eight breeds were selected. According to body size, they were divided into two groups: large chickens and bantam chickens, with four breeds in each group. Firstly, we investigate population structure by principal component analysis (PCA), phylogenetic tree, and ancestry component analysis. Next, we recognize runs of homozygosity (ROH) islands through calculating ROH. Finally, we carry out selection signatures analysis utilizing population differentiation index and nucleic acid diversity. Results The population structure analysis show that large and bantam chickens are clearly separated. Large chickens are clustered together, the bantam chickens are relatively dispersed. The results of ROH island analysis show that 48 and 56 ROH islands were identified in large and bantam chickens respectively. Among the interesting ROH islands, a total of eight candidate genes were identified. In selection signatures analysis, a total of 322 selected genes were annotated in large chickens, such as POU1F1, BMP10, enrichment in 16 gene ontology (GO) terms. In bantam chickens, a total of 447 selected genes were annotated, such as IGF1, GRB10, enrichment in 20 GO terms and 2 Kyoto encyclopedia of genes and genomes pathways. The haplotype analysis results show that GRB10 has differences in chickens of different body sizes. Conclusion By population structure, ROH islands, and selection signatures analysis, we have identified multiple genes associated with chicken body size, growth, and development (such as BMP10, IGF1, GRB10, etc). This provides a theoretical reference for the subsequent development of molecular markers for chicken body size and the analysis of the genetic mechanism of chicken body size.